A Comprehensive Review on Utilizing Nanomaterials in Enhanced Oil Recovery Applications - Jamil Fadi El-Masry; Kamel Fahmi Bou-Hamdan; Azza Hashim Abbas; Dmitriy A. Martyushev (Energies, 2023)
Chemicals are a pivotal part of many operations for the oil and gas industry. The purpose of chemical application in the subsurface reservoir is to decrease the mobility ratio between the displaced fluid and the displacing one or to increase the capillary number. These have been the favorable mechanisms for Enhanced Oil Recovery (EOR). Recently, it became a mainstay with EOR researchers looking for effective and efficient materials that can be economically feasible and environmentally friendly. Therefore, when the development of chemicals reached a peak point by introducing nanosized materials, it was of wondrous interest in EOR. Unlike other sizes, nanoparticles display distinct physical and chemical properties that can be utilized for multiple applications. Therefore, vast amounts of nanoparticles were examined in terms of formulation, size effect, reservoir condition, viscosity, IFT, and wettability alteration. When a holistic understanding of nanoparticles is aimed, it is necessary to review the recent studies comprehensively. This paper reviews the most recently published papers for nanoparticles in oil in general, emphasizing EOR, where most of these publications are between the years 2018 and 2022. It covers a thorough comparison of using nanoparticles in different EOR techniques and the expected range of oil recovery improvements. Moreover, this paper highlights the gaps existing in the field-scale implementation of NPs in EOR and opens space for research and development. The findings of this review paper suggest that the selection of the best NPs type for an EOR application is critical to the reservoir rock properties and conditions, reservoir fluids type, EOR mechanism, chemicals type (surfactant/polymer/alkaline), chemicals concentration used in the flooding process, and NPs properties and concentration.